1980
DOI: 10.1172/jci109830
|View full text |Cite
|
Sign up to set email alerts
|

Effect of D-alanine methionine enkephalin amide on ion transport in rabbit ileum.

Abstract: A B S T R A C T The presence of enkephalins in the intestine and the use of opiates to treat diarrheal diseases suggests that enkephalins may affect intestinal ion transport. Using isolated rabbit ileal mucosa, we found that leucine enkephalin, methionine enkephalin, and D-Ala2-methionine enkephalin amide (D-Ala2-Met E) decreased the short circuit current (ISC) and potential difference although the effect ofD-Ala2-Met E was more pronounced and prolonged. D-Ala2-Met E increased net sodium (+1.27±0.5 pueq/cm2h),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
48
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(58 citation statements)
references
References 25 publications
10
48
0
Order By: Relevance
“…The present study confirms that fi-CM affect intestinal ion transport in the same way as enkephalins since they reduced lsc by a mechanism reversed by naloxone and stimulated Na and CI absorption simultaneously when added to the serosal side of isolated rabbit ileum (Dobbins et aL, 1980;Mc Kay et al, 1981 ). In addition, it appeared that when peptides were added to the luminal side of the intestine, the expression of their opiate activity needs the transfer of an active form to the blood side of the tissue where their receptors are probably located (Tome et al, 1987).…”
Section: Discussionsupporting
confidence: 84%
“…The present study confirms that fi-CM affect intestinal ion transport in the same way as enkephalins since they reduced lsc by a mechanism reversed by naloxone and stimulated Na and CI absorption simultaneously when added to the serosal side of isolated rabbit ileum (Dobbins et aL, 1980;Mc Kay et al, 1981 ). In addition, it appeared that when peptides were added to the luminal side of the intestine, the expression of their opiate activity needs the transfer of an active form to the blood side of the tissue where their receptors are probably located (Tome et al, 1987).…”
Section: Discussionsupporting
confidence: 84%
“…The in vitro effect of DAMA, studied on ileal tissue, has been shown to be associated with a decrease in the short-circuit current (Dobbins et al, 1980;McKay et al, 1981;Binder et al, 1984), suggesting an increase in electrogenic chloride absorption (Dobbins et al, 1980;McKay et al, 1981 Sodium changes were a little at variance with some studies reporting no change (McKay et al, 1981) and others showing an increased absorption (Dobbins et al, 1980) during exposure to enkephalins. In vivo studies (Barbezat and Reasbeck, 1983) revealed a more pronounced increase in net absorption of sodium and bicarbonate during enkephalin infusion in dog than in cat or rat (Coupar, 1978 Our results indicate that DAMA is effective in the cat, as in other species (Cooke, 1986), at 2 different levels of the intestine, jejunum and ileum, even though it is clearly evident that the mechanisms of ion transport differ.…”
Section: Discussionmentioning
confidence: 99%
“…We determined in preliminary experiments the low concentration of sodium and chloride solution which would be suitable for approaching the zero flux ion concentration in both segments (Fromm and Hegel, 1987) An increase in water and ion absorption has been demonstrated following serosal administration of enkephalin in vitro in the rabbit ileum (Dobbins et al, 1980) and in the guinea pig (Kachur et al, 1980), in vivo in the dog (Barbezat and Reasbeck, 1983) and the rat (Fogel and Kaplan, 1984) jejunum. Doses used in the dog (20 gg-kg-1 ·hw) were similar to those used in the cat, and the decrease of ionic concentration of the fluid after absorption was also observed (Barbezat and Reasbeck, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural.8-CM s' present in the [60][61][62][63][64][65][66] fragment of bovine / 3-casein, are characterised by the N-terminal amino-acid sequence Tyr-Pro-Phe-Pro of the [60][61][62][63] fragment. In addition, .8-CM s analogs are prepared by amino-acid substitution and C-terminal amidation to increase opioid potency (Brantl et al, 1982 (Binder et al, 1984 ;Cooke, 1986;Dobbins et al, 1980 ;Cooke et al, 1983 ;Kachur et al, 1980 (Kachur et al, 1980). The results show that the action of the /3-CM analog was neuromediated.…”
mentioning
confidence: 99%